Ethnic enclaves, self-employment and the economic performance of refugees - Henrik Andersson (Uppsala University, Department of Economics, 2018)
In this paper I estimate the causal effect of ethnic enclaves on the probability of self-employment. To account for neighborhood selection I make use of a refugee dispersal program. Results indicate that larger ethnic enclaves, measured as the share of self-employed coethnics in the municipality immigrants first arrive into, effects the probability of self-employment positively, while the share of all other coethnics has a negative effect. Results however also indicate that there is a long term economic penalty to being placed with a larger share of self-employed coethnics, an effect which is partly mediated through the choice of selfemployment.
urn:nbn:se:uu:diva-347043
Keywords: C21; J15; M13; R23; 330; Immigration; Self-employment; Sweden; Foreign born; Ethnic Enclaves; Coethnics